Industrial training report: ZMY Management Services / Zulaika Haroni - Haroni, Zulaika (Universiti Teknologi MARA, Perlis, 2023)
This report provides an overview of the knowledge and skills I gained during my internship with ZMY Management Services, which lasted for six months. ZMY Management Services has been in business for over 20 years, during which time it has been able to provide a diverse selection of services across the nation. This business provides services in the areas of corporate firms' secretaries, corporation and personal income tax, accounting services, and company incorporation. The completion of my industrial training at this organisation has provided me with a number of opportunities and benefits. Aside from that, I am able to study about and gain an understanding of the company's business and services while also getting experience in actual working situations. During the duration of my six-month internship, I successfully conducted the preparation of the company's SWOT analysis. The analysis of strengths, weaknesses, opportunities, and threats. Through the utilisation of SWOT analysis, organisations have the ability to leverage their strengths and capitalise on opportunities, while simultaneously addressing and enhancing their weaknesses and mitigating potential threats. Additionally, the organisation can proactively engage with their competitors in order to increase their opportunities for success. The identification of a company's competitive advantage is a crucial factor in determining the superiority of the services and products it offers in comparison to its competitors. The organisation possesses the capability to discern both the internal and external strengths, as well as the challenges, associated with its competition against other firms.